ANALISIS RASIO LIKUIDITAS DAN RASIO PROFITABILITAS PADA PT SEMEN BATURAJA (PERSERO), TBK - Febi Miharja; Sally Maria Bramana (STIE DWI SAKTI BATURAJA, 2021)
The purpose of this study was to determine the liquidity ratio and profitability ratio in the financial statements of PT Semen Baturaja (Persero) Tbk. The results showed that the current ratio, cash ratio, fast ratio and cash turnover ratio of PT Semen Baturaja (Persero), Tbk in 2015-2019 were above 100%, meaning that PT Semen Baturaja (Persero), Tbk had a very high ability to cover all of its short-term liabilities during 2015-2019. The results of the analysis of the profitability ratio of PT Semen Baturaja (Persero), Tbk show that the average gross profit margin ratio for 2015-2019 is 35.39% which means that every Rp. 1.00 of sales during 2015-2019 can resulting in a gross profit of 35.39%. The average net profit margin ratio (net profit margin) for 2015-2019 was 11.12%, which means that every Rp. 1.00 of sales during 2015-2019 can generate net profit after tax of 11.12%. The average economic profitability ratio (basic earning power) in 2015-2019 was 5.97%, which means that each use of Rp. 1.00 of total assets during 2015-2019 can generate net profit before tax of 5.97%. The average return on investment ratio for 2015-2019 is 4.28%, which means that every Rp1.00 of total assets used can generate an after-tax profit of 4.28%. The average return on equity (return on equity) in 2015-2019 is 5.49%, which means that every Rp. 1.00 of equity used can generate net profit after tax of 5.49%.